لترقية نتائج تعلم اللغة العربية بالمدرسة المتوسطة الإسلامية الحكومية ١ سولوك (Cooperative Integrated Reading and Composition) تطبيق نموذج التعاوني التكاملي في القراءة والإنشاء - Ardiah, Febri; Arsya, Fajriyani; Rizal, Eka; Nurhasnah, Nurhasnah (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
There are problems in learning Arabic, namely the learning process is still centered on the teacher, students have difficulty in reading and writing Arabic texts, and teachers have not used the CIRC model in learning Arabic. Therefore, researchers want to try to apply the CIRC model. The purpose of this study was to determine how to apply the CIRC model and how much influence it has on improving Arabic learning outcomes in eighth grade students of MTsN 1 Solok. Researchers used quantitative research with experimental type. The population in this study is 84 students. Researchers took a sample of 42 people using the purposive sampling method. The data collection tools used observation, test and documentation. The method of data analysis is statistical analysis using SPSS program. The application of the CIRC model was carried out at MTsN 1 Solok. There are influence CIRC model to improve Arabic learning outcomes in eighth grade students and the level of influence is 20.43 or 37.11%. The study found that the Sig 2–Tailed on the hypothesis test was 0.020 and this score was smaller than 0.05. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This shows that there is a difference in the average value between the experimental class and the control class in learning Arabic.. Therefore, it can be concluded that there is an effect of CIRC model on improving Arabic learning outcomes in eighth grade students at MTsN 1 Solok and the level of influence is around 20.43 or 37.11%.